GINGIVOSTOMATITIS IN BALL PYTHON CAUSED BY AEROMONAS HYDROPHILA - Lona Milena; Sri Kayati Widyastuti; I Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2024)
Gingivostomatitis is a disease of digestive system that infects oral cavity, gums, teeth, and palatum that is reported in snakes, lizards, and turtles. This case report describes the case of a 1.5 year old female Ball Python snake that experienced symptoms of anorexia, swollen gums, and difficulty breathing for the past three months. This study aims to provide data and treatment in cases of gingivostomatitis in snakes, particularly in Ball Python. The scientific method in this study was constructed in order to diagnose gingivostomatitis by medical examination such as: physical examination, hematological examination, and microbiological culture and sensitivity test. The results showed that the snake had inverted triangle body which indicates cachexia, sunked and cloudy eyes, coarse scales, lymphocytosis, monocytosis, neutrophilia, and eosinophilia. While microbiological culture and sensitivity test showed that Aeromonas hydrophila was resistant to amoxicillin-clavulanate, ampicillin, and cefazolin. It is necessary to educate owners about the importance of treating diseases early so that the snake's condition does not worsen.